PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DI SEKOLAH DASAR - Lia Sulistianah; M. Taufik; Ana Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Problem Based Learning (PBL) model is one of the learning models that can provide active learning conditions to students by directing students to jointly solve a problem. This researcher aims to find out if there are differences in critical thinking skills between students who use a scientific approach in elementary schools and to find out whether critical thinking skills between students who use the Problem Based Learning (PBL) model are higher than students who use a scientific approach in schools. Base. The subjects of this study were 25 students of class 4A and 25 students of class 4B at SD Negeri Cimuncang Cilik. The research was conducted using quantitative, quasi-experimental methods. The data analysis technique used in this research is descriptive statistical test, normality test, homogeneity test, and hypothesis testing. Based on the descriptive statistical test the control class pretest with an average of 16.88 posttest control class with an average of 8.292 experimental class pretest with an average of 24.68 and posttest experimental class with an average of 30.24. This shows that the critical thinking skills of students who are treated with Problem Based Learning (PBL) are higher than students who are treated with a scientific approach. The results of the independent sample test test were 0.00 <0.05 so that Ho was rejected and Ha was accepted so that it could be concluded that there were differences in critical thinking skills between students who received the Problem Based Learning (PBL) model and students who received the scientific approach